Perencanaan Produksi AMDK 240 ML dengan Metode Trend Liniear - Wiyono, Aprili; Andriyas Puji, Ari (SURYA TEKNIKA, 2023)
PT. Amanah Insanillahia is a company engaged in the field of bottled drinking water (AMDK). PT Amanah Insanillahia produces bottled drinking water under the AMIA brand. In its development, PT Amanah Insanillahia experienced obstacles in certain sectors, for example companies that produce goods without considering market demand, resulting in increased storage costs and also old goods stored will expire. Therefore, to reduce excess storage at PT Amanah Insanillahia, through the discussion in this practical work report, it is necessary to analyse production forecasting using the linear trend method. To meet market needs, the company must know how much sales forecasting will come so that the company can produce goods in accordance with predicted sales. Sales forecasting can help companies minimise costs in producing goods produced, because by knowing some sales in the next period, companies can produce goods in moderation.With the linear trend method.